Serum Scavenging Capacity and Folliculogenesis Impact following Flaxseed Consumption in the First-Generation Mice Pups - Fahimeh Pourjafari; Tahereh Haghpanah; Maria Grazia Palmerini; Massood Ezzatabadipour (Journal of Toxicology)
Flaxseed is a source of antioxidants utilized for female infertility treatment in traditional medicine. This study investigated the effects of flax hydroalcoholic extract and flaxseeds during prenatal and postnatal (PND) periods on folliculogenesis and serum total antioxidant capacity (TAC). Pregnant NMRI mice received 500 and 1000 mg/kg of flax extract (LE) and the same doses of flaxseed (LS). Female pups received the same regimen for 56 days. The body, ovarian morphometry, follicle development, and TAC levels were evaluated. The ovarian weight significantly increased in the LE1000 group compared to the LS500 group. The LE500 group had a considerably lower number of primary and antral follicles compared to the CTL and LS1000 groups. The number of antral follicles significantly increased in the LE1000 group compared to the LS500 and LE500 groups. The number of preovulatory follicles was higher in the LE1000 group. A significant increase in the TAC levels was detected in the LS500, LS1000, and LE1000 groups. LE showed a dose-dependent protective effect on the folliculogenesis in F1, which is more evident with the dosage of 1000 mg/kg. This could be related to the strongest antioxidant property of LE1000, as shown by the highest levels of TAC.